PENINGKATAN HASIL BELAJAR PENGUKURAN WAKTU DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) KELAS III SD - Yati, Rismi Fidra; Ahmad, Syafri; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract This research was conducted since he student learnig result was still low and the approaches used by teacher are not able to make the larning process more meaningful. This research used Realistik teaching approach to improve students learning result. PMRI is a learning approach which teaches the student based on the real life problem then constructing and developing the idea to solve the problem by using quatitative and qualitative approach. The result shows that PMRI approach can improve students learning result from 69.93 in cycle I to 82.65 in cycle II Keywords: Learning result for time measurement. PMRI approach